2018
DOI: 10.1002/jsfa.9139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascophyllum nodosum seaweed extracts on lettuce growth, physiology and fresh‐cut salad storage under potassium deficiency

Abstract: The SW application could alter the detrimental effects of K deficiency during lettuce growth and storage of processed products. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…Similarly, in the present study, a salinity of 100 mmol L –1 NaCl, even in the short‐term (up to 10 days), retarded petunia plant growth because several growth (biomass) and physiological (stomatal closure, chlorophylls fluorescence) parameters were decreased. Moreover, the effects of saline only reflected metabolic changes in petunia flowers, and not in leaves, because not only polyphenols and antioxidants, but also carotenoids and anthocyanins increased in flowers to scavenge the ROS accumulation as a result of saline stress . The results of the present study showed that unchanged levels of polyphenols and antioxidants in leaves might not reflect the metabolic changes in flowers.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Similarly, in the present study, a salinity of 100 mmol L –1 NaCl, even in the short‐term (up to 10 days), retarded petunia plant growth because several growth (biomass) and physiological (stomatal closure, chlorophylls fluorescence) parameters were decreased. Moreover, the effects of saline only reflected metabolic changes in petunia flowers, and not in leaves, because not only polyphenols and antioxidants, but also carotenoids and anthocyanins increased in flowers to scavenge the ROS accumulation as a result of saline stress . The results of the present study showed that unchanged levels of polyphenols and antioxidants in leaves might not reflect the metabolic changes in flowers.…”
Section: Discussioncontrasting
confidence: 55%
“…Plants have adapted mechanisms to resist, to some extent, salinity stress and, amongst such mechanisms, stomatal closure and a decrease in metabolic processes usually occur. 12,38,39 Izadi-Darbandi and Mehdikhani 40 reported a reduction of stomatal conductance in Plantago spp. when subjected to salinity in the range 50-250 mmol L -1 NaCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main benefits of biostimulants applied directly in the soil, such as arbuscular mycorrhizal fungi, plant growth‐promoting rhizobacteria and other nonpathogenic fungi, are associated with improved soil water‐holding capacity and root conformation, increased root growth accompanied by more effective nutrient and water uptake, and, most importantly, with increased yield . Other products, such as seaweed extracts, protein hydrolysates, and plant extracts, stimulate plant growth mostly through their bioactive ingredients, although soil improvement properties have also been reported in terms of physicochemical properties of soil matrix …”
Section: Introductionmentioning
confidence: 99%
“…10 Other products, such as seaweed extracts, protein hydrolysates, and plant extracts, stimulate plant growth mostly through their bioactive ingredients, although soil improvement properties have also been reported in terms of physicochemical properties of soil matrix. 10,11 The past decade has evidenced an increased use of biostimulants in the farming sector in general and in intensive production systems, such as horticultural cropping systems, in particular. 12,13 Apart from the evident goal for an increased yield through the use of biostimulants, their effects on product quality are equally important, and several reports have highlighted the improvement in quality of various horticultural crops, such as spinach 14 , strawberry, 15 and tomato.…”
Section: Introductionmentioning
confidence: 99%